Information architecture for business processes and database modeling - Brandt, Mariana Baptista; Vidotti, Silvana Aparecida Borsetti Gregorio (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
Data and information produced and consumed uninterruptedly in institutions need to go through effective information management and data governance processes, whether due to internal necessity or legal compliance. This research aims to verify the feasibility of integrating Information Science methods with those already used in the process of modeling databases in Computer Science, for the creation of databases in information systems. For that, applied research is carried out, involving the modeling of a database for an application together with the modeling of the information of this application, using the methodology of Information Architecture for Business Processes. The present work identifies intersections between the methodologies, observing the correspondence between the business metadata element of the Architecture for Business Processes and the entity attribute element of the databases. This result allows us to conclude that there is adherence between the methodologies and, by adding the Architecture for Business Processes implementation to the database modeling, it is possible to trace the lineage of the data and information, from the database to the business process.
Keywords: database modeling; information architecture for business processes; data catalog; data governance